2018
DOI: 10.3892/ol.2018.9490
|View full text |Cite
|
Sign up to set email alerts
|

High levels of glioma tumor suppressor candidate region gene 1 predicts a poor prognosis for prostate cancer

Abstract: Glioma tumor suppressor candidate region gene 1 (GLTSCR1) is associated with the progression of oligodendroglioma. However, there has been little study of GLTSCR1 in prostate cancer. In the present study, the association between the expression of GLTSCR1, and the progression and prognosis of tumors in patients with prostate cancer was assessed. An immunohistochemical analysis was performed using a human tissue microarray for GLTSCR1 at the protein expression level and the immunostaining results were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…For instance, forkhead transcription factor (FoxM1) functions as an oncogene in the initiation, development, and progression of cancer, and its neoplastic functions can be used as a strong biomarker for the diagnosis and treatment of cancer (21). In prostate cancer, numerous prognostic biomarkers were also investigated (22)(23)(24). For instance, minichromosome maintenance 10 replication initiation factor (MCM10) was revealed to be significantly upregulated in prostate cancer patients, and overexpression of MCM10 promoted cell proliferation and predicted poor prognosis in prostate cancer (25).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, forkhead transcription factor (FoxM1) functions as an oncogene in the initiation, development, and progression of cancer, and its neoplastic functions can be used as a strong biomarker for the diagnosis and treatment of cancer (21). In prostate cancer, numerous prognostic biomarkers were also investigated (22)(23)(24). For instance, minichromosome maintenance 10 replication initiation factor (MCM10) was revealed to be significantly upregulated in prostate cancer patients, and overexpression of MCM10 promoted cell proliferation and predicted poor prognosis in prostate cancer (25).…”
Section: Discussionmentioning
confidence: 99%
“…A total of five representative fields were microscopically observed (magnification, x400) and the number of positively-stained cells was enumerated. Cytoplasmic and nuclear staining was regarded as positive according to the antibody specification sheet (18). The expression level of MBTD1 in each sample was semi quantitatively scored depending on the staining intensity and percentage of stained cells.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to brain tumors, recent work has elucidated a wider range of cancer associations with GLTSCR1. After it was found that several loci associated with prostate cancer aggressiveness were located on chromosome 19 [ 101 , 102 ], the same chromosome of interest in the aforementioned brain tumor studies, the presence of GLTSCR1 on this chromosome was an indicator for a potential link between prostate cancer and GLTSCR1 [ 103 ]. Indeed, the same study revealed that the expression of GLTSCR1 protein had a striking association with advanced clinical stage, enhanced tumor invasion, and lymph node and distant metastasis in prostate cancer tissue samples.…”
Section: Gbaf and Its Subunits In Mammalian Diseasementioning
confidence: 99%
“…Indeed, the same study revealed that the expression of GLTSCR1 protein had a striking association with advanced clinical stage, enhanced tumor invasion, and lymph node and distant metastasis in prostate cancer tissue samples. Interestingly, the authors noted that prostate cancer patients with high expression levels of GLTSCR1 had a significantly shorter life expectancy when compared to prostate cancer patients with lower expression [ 103 ]. Knockout of GLTSCR1 in metastatic prostate cancer cell line PC3 resulted in a noticeable decrease in both colony formation and proliferation in this cell type, and similar effects were observed following GLTSCR1L knockout, suggesting a dependency of PC3 cells on GLTSCR1 and GLTSCR1L [ 27 ].…”
Section: Gbaf and Its Subunits In Mammalian Diseasementioning
confidence: 99%